PROPOSED INTEGRATED MARKETING COMMUNICATION STRATEGY FOR ELECTRONIC HOME APPLIANCES PRODUCT: STUDY OF SHARP ELECTRONICS INDONESIA - Mahesa Putra, Adam
Indonesia is a country with a high population of total 267,538,016, it brings great influence to the economic growth with household consumption that is expended. Since the Covid-19 pandemic occurred, the level of household consumption has decreased and resulting to a negative growth in economic growth in Indonesia, with minus 5.51 in Q2 and minus 3.49 in Q3. This condition also affects the manufacturing industry, especially electronic home appliances products such as refrigerators, air conditioners, washing machines and televisions with market decrement by November 2020 is -2.1% for refrigerators, -4.3% for air conditioners, -3.8 for televisions and while for washing machines are still experiencing positive growth in the market by 7.6%.